2020
DOI: 10.3390/jcm9082387
|View full text |Cite
|
Sign up to set email alerts
|

Combined Surgical and Orthodontic Treatments in Children with OSA: A Systematic Review

Abstract: Obstructive sleep apnea (OSA) is a sleeping breathing disorder. In children, adenotonsillar hypertrophy remains the main anatomical risk factor of OSA. The aim of this study was to assess the current scientific data and to systematically summarize the evidence for the efficiency of adenotonsillectomy (AT) and orthodontic treatment (i.e., rapid maxillary expansion (RME) and mandibular advancement (MA)) in the treatment of pediatric OSA. A literature search was conducted in several databases, including PubMed, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Templier et al evaluated the evidence for the efficiency of AT and orthodontic treatment in a systematic review, and stated that AT-combined orthodontic treatments (RME and/or MAD) were more effective together than separately to cure OSA in paediatric patients. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Templier et al evaluated the evidence for the efficiency of AT and orthodontic treatment in a systematic review, and stated that AT-combined orthodontic treatments (RME and/or MAD) were more effective together than separately to cure OSA in paediatric patients. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews and meta-analyses about OSA treatments have been reported, but the comparison of the different treatments is very limited. Templier et al evaluated the evidence for the efficiency of AT and orthodontic treatment in a systematic review, and stated that AT-combined orthodontic treatments (RME and/or MAD) were more effective together than separately to cure OSA in paediatric patients 29…”
Section: Discussionmentioning
confidence: 99%
“…A combination of AT and dental interventions might be more effective in patients than performed separately. 128 Mandibular distraction osteogenesis is one of the maxillo-mandibular surgeries performed for children with congenital craniofacial abnormalities such as Pierre Robin sequence or Treacher Collins syndrome. 123 These interventions should be co-ordinated by a multidisciplinary team, preluded by and followed-up with sleep studies.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…TA together with orthodontic treatment is considered more effective together than separately for SDB in pediatric patients, however, recurrence of SDB may occur several years later. To prevent recurrence, myofunctional therapy could be recommended as a follow-up, however, more studies with good clinical evidence are required to confirm this finding [31] . The childhood adenotonsillectomy trial demonstrated improvement in PSG metrics, as well as secondary behavioral and quality of life outcomes, in both obese and non-obese children with PSGdiagnosed OSA [29] .…”
Section: Treatmentmentioning
confidence: 99%